PENINGKATAN MINAT BELAJAR SISWA KELAS VIII PADA MATA PELAJARAN AQIDAH AKHLAK DI MTs. AL-HAFIZH RAJEG KABUPATEN TANGERANG - basyit, abdul; Harahap, Erpin; Gumelar, R Tommy; Rowinex, Putri (ISLAMIKA, 2021)
Abstract; The importance of interest in learning for students. refers to an increase in student interest in learning which also affects student success. With the interest in students learning activities will arise. Students with great interest will be able to carry out all their learning activities seriously. It is in line with the case that occurred in Mts Al-Hafizh, where many students are less enthusiastic in following lessons, especially in the subject of Aqidah Morals. This is not the case in most Tsanawiyah Madrasas. Thereore it is necessary to do research related to increasing the interest in learning of VIIIth grade students in the subject of Aqidah Morals in MTs Al-Hafizh Rajeg Tangerang.